A Paired RNAi and RabGAP Overexpression Screen Identifies Rab11 as a Regulator of β-Amyloid Production - Vinod Udayar (Cell Reports, 2013)
Alzheimer’s disease (AD) is characterized by cerebral deposition of β-amyloid (Aβ) peptides, which are generated from amyloid precursor protein (APP) by β- and γ-secretases. APP and the secretases are membrane associated, but whether membrane trafficking controls Aβ levels is unclear. Here, we performed an RNAi screen of all human Rab-GTPases, which regulate membrane trafficking, complemented with a Rab-GTPase-activating protein screen, and present a road map of the membrane-trafficking events regulating Aβ production. We identify Rab11 and Rab3 as key players. Although retromers and retromer-associated proteins control APP recycling, we show that Rab11 controlled β-secretase endosomal recycling to the plasma membrane and thus affected Aβ production. Exome sequencing revealed a significant genetic association of Rab11A with late-onset AD, and network analysis identified Rab11A and Rab11B as components of the late-onset AD risk network, suggesting a causal link between Rab11 and AD. Our results reveal trafficking pathways that regulate Aβ levels and show how systems biology approaches can unravel the molecular complexity underlying AD.